Nurses' perceptions of the challenges related to the Omanization policy. (16th November 2015) - Al‐Riyami, M.; Fischer, I.; Lopez, V.
Abstract : Background: Human resource development has become a major concern in Oman since the inception of the 'Omanization' policy in 1988. The main goal of this policy was to replace the expatriate nursing workforce with similarly qualified local nurses to develop a sustainable workforce and achieve self‐reliance. Aim: The aim of this study is to explore the nurses' perceptions of Omanization policy. Methods: A qualitative research design was used and 16 Omani registered nurses and 26 student nurses were interviewed indepth. Transcribed data were analysed using content analysis. Results: Two main themes emerged from the data: 'Challenges of sustaining the local nursing workforce' and 'Challenges of educational preparation for local nurses'. The participants agreed that Omanization benefited national development, social stability and ensuring local workforce. The challenges faced were cultural and work life balance, preparation of nurses and pace of replacement. Conclusion: The participants were concerned that the pace of replacement could leave behind a marked experience gap. A slow‐phased approach to Omanization of the nursing workforce was recommended by the participants. Limitations: Results obtained from this study reflect the perceptions and voices of student nurses and registered nurses only from the Institute of Nursing and Oman Ministry of Health. Implications for nursing education and policy: A policy of this magnitude requires gradual establishment. The upgrading of the nursing education to degree level, continuous professional development, mentoring and role modeling of expert nurses should be established to prepare local nurses for the localization of the nursing workforce.